Imaging Modalities for Evaluating Lymphedema - Bendeguz Istvan Nagy; Balazs Mohos; Chieh-Han John Tzou (Medicina, 2023)
Lymphedema is a progressive condition. Its therapy aims to reduce edema, prevent its progression, and provide psychosocial aid. Nonsurgical treatment in advanced stages is mostly insufficient. Therefore—in many cases—surgical procedures, such as to restore lymph flow or excise lymphedema tissues, are the only ways to improve patients’ quality of life. Imaging modalities: Lymphoscintigraphy (LS), near-infrared fluorescent (NIRF) imaging—also termed indocyanine green (ICG) lymphography (ICG-L)—ultrasonography (US), magnetic resonance lymphangiography (MRL), computed tomography (CT), photoacoustic imaging (PAI), and optical coherence tomography (OCT) are standardized techniques, which can be utilized in lymphedema diagnosis, staging, treatment, and follow-up. Conclusions: The combined use of these imaging modalities and self-assessment questionnaires deliver objective parameters for choosing the most suitable surgical therapy and achieving the best possible postoperative outcome.